A multifunctional epoxy structural adhesive with superior flexibility, damping and durability. (22nd November 2021) - Ge, Ying; Zhang, Xueqin; Shi, You; Cai, Yuanbo; Zhou, Shengtai; Liang, Mei; Zou, Huawei
Abstract : In this work, we introduced MCA with a flexible long chain into epoxy resin, and the elongation at break of MCA cured epoxy resin was over 200%. Abstract : In this work, a modified curing agent (MCA) with a flexible long chain and semi-aromatic amide units was synthesized using M-benzoyl chloride and polyether amine (D-230 and D-400), and then innovatively incorporated into epoxy to prepare a multifunctional epoxy structural adhesive with superior flexibility, damping and durability. It was shown that the strength of the MCA modified epoxy thermosets was 18 MPa, and the elongation at break was significantly improved to 17.9 times higher than that of the control blending samples (D-230, D-230&D-400 and D-400). Meanwhile, the MCA modified epoxy resin exhibited great damping behavior; its damping temperature range was from 24.3 °C to 81.6 °C, suggesting that it was a good damping material. After three stretch–recovery cycles, over 97% of the tensile strength of the MCA modified epoxy was still maintained, indicating that it has good stress fatigue durability. This new multifunctional epoxy adhesive significantly broadened the usage of epoxy and has the potential for use as a high damping adhesive in the automotive and aerospace fields.